Extracellular vesicles: Novel mediator for cell to cell communications in liver pathogenesis. (April 2018) - Devhare, Pradip B.; Ray, Ratna B.
Abstract: Extracellular vesicles (EVs) are membrane derived nanometer-sized vesicles. EVs are released by normal, diseased, and transformed cells in vitro and in vivo, and carry lipids, proteins, mRNAs, non-coding RNAs, and even DNA out of cells. Transferring biological information via EVs to neighboring cells and inter-cellular communication not only maintain physiological functions, but also involve in the pathogenesis of several diseases, including cancer. The aim of this review is to discuss the emerging role of EVs in viral hepatitis, non-alcoholic or alcoholic liver disease and liver cancers. We summarize what is known about exosome biogenesis, and role in liver disease progression, and discuss the potential clinical applications of EVs as predictive biomarkers and therapeutic modalities.